PENDIDIKAN ISLAM BERBASIS MASJID: STUDI LITERATUR ATAS FUNGSI MASJID SEBAGAI INSTITUSI EDUKASI - M. Lutfiatul Hasan; Adam Hafidz Al Fajar (Journal Islamic Studies, 2025)
This study aims to comprehensively explore how mosques have fulfilled and can further develop their function as educational institutions in Islamic education. Using a qualitative approach and literature review method, this research examines various relevant academic references from journals, books, and other scholarly publications over the past ten years. The findings indicate that since the time of Prophet Muhammad (PBUH), the mosque has served as a center for education and community empowerment, encompassing spiritual, social, and intellectual dimensions. In the contemporary context, mosques carry out educational functions through programs such as Qur’anic learning centers (TPA), madrasah diniyah, Islamic study groups (majelis taklim), thematic lectures, Islamic skills training, and the integration of digital technology in learning. Mosques also serve as hubs for youth development and community building, fostering character formation and strengthening Islamic brotherhood. The success of mosque-based education largely depends on management quality, community participation, and innovation in both learning methods and media. This study concludes that mosques have great potential to serve as contextual, inclusive, and sustainable Islamic educational institutions. Therefore, revitalizing the mosque's role as a learning and community development center is essential to meet the needs of the modern era.